The Phenomenon of the Tradition of Reciting Qur'anic Verses in the Awrad Kitab Dzikrul Ghofilin in the Jakatawa Mosque Community Sang Cipta Rasa - Hamid, Abdul; Yahya, Mohamad; Nawawi, Fuad (IAIN Manado, 2025)
Abstract: Zikr is a human practice in an effort to get closer to Allah Swt. Along with the times, this dhikr reading product develops dynamically according to the direction of each Mursyid. One of the dhikr that is studied is the awrad Kitab Dzikrul Ghofilin. This article aims to describe and identify the community's meaning of the recitation of Qur'anic verses contained in the awrad Kitab Dzikrul Ghofilin. This research uses a qualitative method with the Interpretative Phenomenological Analysis (IPA) theory approach initiated by Jonathan A. Smith. The results showed that the polarization of expression in the community was inseparable from the existence of the verses of the Holy Qur'an in the awrad of Kitab Dzikrul Ghofilin delivered by the scholars, such as: responsibility as motivation; ingenuity in broadcasting the awrad; a sense of tawadhu and simplicity; comfort, tranquility, and peace of heart: collaboration of taste; and finally the pleasure of Allah Swt. as hope. Furthermore, the impact felt by the practitioners of the awrad Kitab Dzikrul Ghofilin, namely activities feel lighter and less difficult, the arrival of unexpected sustenance, all affairs are facilitated, and more careful in their behavior. This research is expected to give birth to a number of new expressions in responding to traditions that develop in society and recommends that stakeholders always take care of traditions that have nuances of mysticism.Keywords: Al-Qur'an, Awrad Kitab Dzikrul Ghofilin, Phenomenology, Zikir Abstrak: Zikir merupakan pegangan amalan manusia dalam upaya mendekatkan diri kepada Allah Swt. Seiring perkembangan zaman, produk bacaan zikir ini berkembang secara dinamis sesuai arahan Mursyidnya masing-masing. Salah satu zikir yang dikaji ialah awrad Kitab Dzikrul Ghofilin. Artikel ini bertujuan untuk mendeskripsikan dan mengidentifikasi pemaknaan komunitas terhadap pembacaan ayat-ayat Al-Qur’an yang terdapat dalam awrad Kitab Dzikrul Ghofilin. Penelitian ini menggunakan metode kualitatif dengan pendekatan teori Interpretative Phenomenological Analysis (IPA) yang digagas oleh Jonatan A. Smith. Hasil penelitian menunjukkan bahwa polarisasi ekspresi pada komunitas tidak terlepas dari adanya fadilat-fadilat ayat suci Al-Qur’an pada awrad Kitab Dzikrul Ghofilin yang disampaikan oleh para ulama, seperti: tanggung jawab sebagai motivasi; kecerdikan dalam mensyiarkan awrad; rasa tawadhu dan kesederhanaan; kenyamanan, ketenangan, dan kedamaian hati: kolaborasi olah rasa; dan terakhir rida Allah Swt. sebagai harapan. Selanjutnya dampak yang dirasakan oleh pengamal awrad Kitab Dzikrul Ghofilin, yaitu aktivitas terasa lebih ringan dan tidak sulit, datangnya rezeki yang tidak terduga-duga, segala urusan dipermudah, dan lebih berhati-hati dalam bersikap. Penelitian ini diharapkan melahirkan sejumlah ekspresi-ekspresi baru dalam merespon tradisi yang berkembang di masyarakat dan merekomendasikan kepada stakeholder agar senantiasa merawat tradisi yang bernuansa aliran kebatinan. Kata Kunci: Al-Qur’an, Awrad Kitab Dzikrul Ghofilin, Fenomenologi, Zikir